A POSSIBLE LONG-TERM CO2 SINK THROUGH SUBMARINE WEATHERING OF DETRITAL SILICATES - Aloisi G.; Wallmann K.; Tishchenko P.; Haeckel M.; Pavlova G.; Greinert J.; Eisenhauer A. (My University, 2006)
The weathering of silicate minerals exposed on the continents is the largest sink of atmospheric CO 2 on time scales of millions of years. The rate of this process is positively correlated with global mean temperature and atmospheric CO 2 concentration, resulting in a negative feedback that stabilizes Earths' climate (Berner, 2004). Detrital silicates derived from the physical denudation of the continents are a major component of marine sediments (Li and Schoonmaker, 2003). However, their geochemical behaviour is poorly understood and they are considered to be unimportant to the long-term carbon cycle. We show that in organic matter-rich sediments of the Sea of Okhotsk detrital silicates undergo intense weathering. This process is likely favoured by microbial activity, which lowers pore water pH and releases dissolved humic substances, and by the freshness of detrital silicates which origi-nate from the cold, poorly weathered Amur River basin. Numer-ical simulations of early diagenesis show that submarine weathering rates in our study area are comparable to average con-tinental weathering rates (Gaillardet et al., 1999). Furthermore, silicate weathering seems to be widespread in organic matter-rich sediments of continental margins, suggesting the existence of a significant CO 2 sink there. These findings imply a greater efficien-cy of the silicate weathering engine also at low surface tempera-tures, resulting in a weakening of the negative feedback between pCO 2 , climate evolution and silicate weathering.
Keywords: SUBMARINE WEATHERING